FAKTOR DOMINAN YANG MEMPENGARUHI KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA REMAJA PUTRI 15-18 TAHUN DI JAWA TENGAH : ANALISIS DATA SEKUNDER RISKESDAS 2018 - Agita Ayu Widiani, (2023)
Background: Chronic Energy Deficiency (CED) is a condition when a person experiences nultritional deficiencies that last for years (chronic), caulsing health problems. According to (WHO, 2017), complications of CED problems are higher in adolescent girls aged 10 to 19 years. In Indonesia, 36.3% of adolescent girls affected by CED are in the age range of 15-19 years. According to the results of data from Riskesdas 2018, in 2007 CED in non-pregnant adolescent girls was 30.9%, bult in 2013 it rose to 46.6%, and in 2018 it decreased again by 36.3%. One of the provinces in Indonesia with the highest prevalence of CED in adolescent girls is Central Java Province. Based on the results (RISKESDAS, 2018), the prevalence of CED in Central Java Province among adolescent girls was 18.2%. The prevalence of CED among adolescent girls aged 15-18 years in Central Java Province is said to be qulite high at 18.2%, exceeding the national prevalence of 14.5%. Objective: This study aimed to determine the dominant factors influencing the incidence of CED among adolescent girls 15-18 years old in Central Java. Methods: This type of research is observational analytic with cross sectional design ulsing secondary data of RISKESDAS 2018. Results: The bivariate results in this stuldy showed that factors significantly associated with the incidence of CED inclulded the age of the respondent (p-valule 0.000), the respondent's edulcational statuls (p-valule 0.003), and nultritional statuls (p-valule 0.000). The bivariate results in this stuldy showed that the dominant factors that were significantly associated with the incidence of CED inclulded the age of respondents (p-valule 0.000 and OR 0.574) and the nultritional statuls of respondents (p-valule 0.000 and OR 46.93). Conclusion: Nultritional statuls has a risk of 47 times greater than the age of respondents who only have a risk of 0.57 for the incidence of CED. So it can be said that the relationship that occulrs between nultritional statuls and the incidence of CED in this stuldy is strong.